2022
DOI: 10.1371/journal.pone.0269378
|View full text |Cite
|
Sign up to set email alerts
|

Additive genetic effect of GCKR, G6PC2, and SLC30A8 variants on fasting glucose levels and risk of type 2 diabetes

Abstract: Impaired glucose tolerance is a major risk factor for type 2 diabetes (T2D) and several cardiometabolic disorders. To identify genetic loci underlying fasting glucose levels, we conducted an analysis of 9,232 individuals of European ancestry who at enrollment were either nondiabetic or had untreated type 2 diabetes. Multivariable linear mixed models were used to test for associations between fasting glucose and 7.9 million SNPs, with adjustment for age, body mass index (BMI), sex, significant principal compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Visceral obesity and high BMI were high risk factors, especially in both metabolic disorders. Previous studies indicated that the prevalence of obesity usually surpassed 90% of the subjects in NAFLD [ 8 ]. The development of obesity was also significantly linked with the GCKR rs1260326 mutant allele (C) especially in NAFLD subjects, while the frequency of mutant allele (C) was considerably higher in T2DM obese subjects but did not show a statistical significance in comparison to normal weight subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visceral obesity and high BMI were high risk factors, especially in both metabolic disorders. Previous studies indicated that the prevalence of obesity usually surpassed 90% of the subjects in NAFLD [ 8 ]. The development of obesity was also significantly linked with the GCKR rs1260326 mutant allele (C) especially in NAFLD subjects, while the frequency of mutant allele (C) was considerably higher in T2DM obese subjects but did not show a statistical significance in comparison to normal weight subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The GCKR rs1260326 genetic variant is functionally relevant comprising of an amino acid substitution as C to T coding for a proline-to-leucine at position 446 (P446L) (Supplementary Figure 1 ) [ 7 ]. A missense variant in the GCKR rs1260326 is associated with abnormal fasting glucose levels and a higher risk of T2DM development [ 8 ]. Similarly, genome-wide association studies (GWASs) also reported that functional variants of the GCKR including rs1260326 are associated with low plasma insulin and fasting plasma glucose, as well as higher fasting and postprandial serum triglyceride levels [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…From a paradigm of protein sequence-to-structure-to-function, we uploaded translated sequences (amino acid sequences) to the I-TASSER online server ( , accessed on 19 October 2022) [ 26 , 27 , 28 ] to predict the three-dimensional (3D) protein structure. We used the protein 3D structure to find matches in a protein function database in order to predict protein functions [ 29 ]. PyMol [ 30 ] was used to view and analyze the protein structure.…”
Section: Methodsmentioning
confidence: 99%